Tuning the magnetic properties of hydrogenated bilayer graphene and graphene/h-BN heterostructures by compressive pressures. (May 2018) - Moaied, Mohammed; Hong, Jisang
Abstract: We investigated the electronic structure and magnetic properties of hydrogenated bilayer graphene and graphene/h-BN heterostructure as a function of applied uniaxial compression normal to the interface plane using van der Waals density functional theory. The H atoms preferred a cluster formation was found in the hydrogenated bilayer graphene and graphene/h-BN systems with a non-magnetic ground state. With increasing external pressure, the equivalence of two sublattices in graphene was broken because of the interaction between graphene and the underlying layer and the site dependent adsorption energy difference was greatly enhanced with the applied pressure. This resulted in a transition from an NM ground state to a ferromagnetic in hydrogenated bilayer graphene and graphene/h-BN heterostructure. Thus, we propose that the magnetic property can be manipulated by external pressure and that hydrogenated systems can be utilized for potential spintronics applications at low H concentrations. Graphical abstract: Image 1